The influence of musculoskeletal forces on the growth of the prenatal cortex in the ilium: a finite element study. Issue 13 (2nd October 2020) - Watson, Peter J.; Fagan, Michael J.; Dobson, Catherine A.
Abstract: Remodelling and adaptation of bone within the pelvis is believed to be influenced by the mechanical strains generated during locomotion. Variation in the cortical bone thickness observed in the prenatal ilium has been linked to the musculoskeletal loading associated with in utero movements; for example the development of a thicker gluteal cortex is a possible response to contractions of the gluteal muscles. This study examines if the strains generated in the prenatal iliac cortex due to musculoskeletal loading in utero are capable of initiating bone remodelling to either maintain homeostasis or form new bone. Computational modelling techniques were used firstly to predict the muscle forces and resultant joint reaction force acting on the pelvis during a range of in utero movements. Finite element analyses were subsequently performed to calculate the von Mises strains induced in the prenatal ilium. The results demonstrated that strains generated in the iliac cortex were above the thresholds suggested to regulate bone remodelling to either maintain homeostasis or form new bone. Further simulations are required to investigate the extent to which the heterogeneous cortex forms in response to these strains (i.e., remodelling) or if developmental bone modelling plays a more pivotal role.